Perceptions of perinatal alcohol use and treatment needs in Cape Town, South Africa: a qualitative study - Petersen Williams, Petal; Erasmus-Claassen, Lesley-Ann; Taylor, Shantae; Browne, Felicia A.; Wechsberg, Wendee M.; Myers, Bronwyn; Parry, Charles D. H.; Washio, Yukiko (Frontiers in Psychiatry, 2024)
Background South Africa has one of the world’s highest rates of foetal alcohol spectrum disorders (FASD). Recent evidence also showed that alcohol use during lactation significantly compromises child development in children exposed to alcohol through breastfeeding, independent of prenatal alcohol exposure. This study explored perceptions of perinatal alcohol use and treatment needs in Cape Town, South Africa, to inform the development of an intervention to encourage alcohol abstinence during pregnancy and breastfeeding. Methods Individual in-depth interviews (IDIs) were conducted with women who were pregnant with a recent history of alcohol use (n=32) and clinic and community stakeholders (n=16). Interviews were audio recorded and transcribed verbatim. Coding and thematic analyses were conducted in NVivo 12. Results Results indicate widespread perception that women know the dangers of drinking alcohol while pregnant with much less known about drinking while breastfeeding. Mixed views were shared about whether women who are pregnant or breastfeeding experience alcohol-related stigma. Participants described contextual factors impacting drinking that include interpersonal violence, lack of support, stress, anxiety and poverty, and drinking being normalised. Finally, participants had mixed views and conflicting knowledge of available resources to support alcohol reduction and highlighted a desire for support groups and the involvement of partners in alcohol interventions. Conclusions Findings from this study highlight the need for an alcohol intervention programme that is innovative and tailored to the needs of women who are pregnant or postpartum. It also highlights the importance of including community-based support and partner involvement in these interventions.